2020
DOI: 10.1111/jcpt.13243
|View full text |Cite
|
Sign up to set email alerts
|

Renal safety and efficacy of angiotensin receptor‐neprilysin inhibitor: A meta‐analysis of randomized controlled trials

Abstract: What is known and objective Angiotensin receptor‐neprilysin inhibitor (ARNi) therapy has been shown to improve cardiovascular outcomes in the Prospective Comparison of ARNi with angiotensin‐converting enzyme inhibitor to Determine the Impact on Global Mortality and Morbidity in Heart Failure (PARADIGM‐HF) study. However, the renal safety and efficacy of ARNi remains controversial. This meta‐analysis aimed to assess the renal safety and efficacy of angiotensin receptor‐neprilysin inhibitor (ARNi). Methods and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Furthermore, CKD did not show to have a significant impact on S/V uptitration. This is in line with data from the PARADIGM-HF and related clinical trials, which have suggested that S/V offers greater renal protection compared with RAAS inhibition alone, while maintaining the beneficial effects on cardiovascular morbidity/mortality and clinical symptoms [ 7 , 8 , 9 , 10 ]. As opposed to most of these clinical trials, this study did not restrict the included population to patients with eGFR ≥ 30 mL/min/1.73 m 2 , but also included patients with eGFR of 15 to 29 mL/min/1.73 m 2 , in an attempt to add a bit more understanding on the effectiveness and tolerability of S/V in HFrEF patients with severe CKD.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, CKD did not show to have a significant impact on S/V uptitration. This is in line with data from the PARADIGM-HF and related clinical trials, which have suggested that S/V offers greater renal protection compared with RAAS inhibition alone, while maintaining the beneficial effects on cardiovascular morbidity/mortality and clinical symptoms [ 7 , 8 , 9 , 10 ]. As opposed to most of these clinical trials, this study did not restrict the included population to patients with eGFR ≥ 30 mL/min/1.73 m 2 , but also included patients with eGFR of 15 to 29 mL/min/1.73 m 2 , in an attempt to add a bit more understanding on the effectiveness and tolerability of S/V in HFrEF patients with severe CKD.…”
Section: Discussionsupporting
confidence: 85%
“…Some recent publications suggest that S/V in patients with CKD may offer great renal protection while maintaining beneficial effects on cardiovascular events, compared with renin-angiotensin-aldosterone system (RAAS) inhibition alone [ 8 , 9 , 10 ], supporting the beneficial effect of ARNI in HFrEF patients with CKD. As a result of the lack of data on the efficacy and tolerability of S/V in HFrEF patients with severe CKD, the current recommendation is to initiate S/V with caution in patients with eGFR < 30 mL/min/1.73 m 2 , starting at the lowest dose twice daily and not to use the drug in patients with end-stage renal disease (eGFR < 15 mL/min/1.73 m 2 ) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the incidence of hyperkalemia was significantly lower in the ARNI group than in the valsartan group (13.2 vs. 15.3%, P = 0.048) ( 30 ). A meta-analysis of 11 randomized controlled trials comparing ARNI with RAAS inhibitors showed that, compared with those receiving ACEI/ARB, the ARNI group had a slightly lower risk of hyperkalemia (RR = 0.95; 95% CI = 0.88–1.02) ( 71 ). A meta-analysis published in ASN in 2020 showed similar results ( 72 ); however, patients with heart failure were mainly included in these studies, whereas patients with eGFR <30 mL/min/1.73 m 2 or serum creatinine level > 221 μmol were excluded.…”
Section: Use Of Arni In Non-dialysis Patients With Ckdmentioning
confidence: 99%
“…Recently, a new approach for the treatment of CKD has been proposed—the use of a combination of the neprilysin inhibitor (sacubitril), which inhibits the cleavage of natriuretic peptides, and the AT1 antagonist valsartan (ARNI—angiotensin receptor AT1 and neprilysin inhibition). This combination of drugs showed a positive effect on the suppression of the development of TF and glomerulosclerosis in rats [ 149 ] and in clinical studies of acute renal pathologies treatment; however, it is necessary to confirm the positive effects in patients with CKD [ 150 ].…”
Section: Hormone Therapy Of Fibrosismentioning
confidence: 99%